IMPLIKASI DISTORSI DEMOKRASI PADA PEMILUKADA TERHADAP PENGUATAN DEMOKRASI LOKAL - Sinaga, Rudi Salam (Universitas Medan Area, 2013)
Indonesia to start the general election of regional heads (Election first implemented in 2005, from the results of research that has been done by M.Iksan in the know in generalelections in 2005 which carried on wel run, orderly, safe, smooth and democratic. Soebagio research results conducted in the year after the year 2004 and 2009 indicatethe occurrence of distortion in the transition to democracy in Indonesia with the mark of democracy is only able to move in a procedural-electora dimensions have not touched the substantial aspects. Journey's transition to democracy in Indonesia has a new persolan when the distortion is giving its implications for strengthening local democracy in Indonesia. This study uses descriptive evaluative. The results of this study found a strong relationship of understanding the implications of the distortion of democracy that is limited to the dimensions of proceduraldemocracy-electoral posed a serious threat to the strengthening of local democracy inIndonesia where the practice of transactional relationships between the contestants andkonsituen as the implications of procedural-electoral democracy.